Corporate Social Responsibility and Leadership - Dutta, P. K. (Prabandhan: Indian Journal of Management, 2010)
In a LPG (liberalization, privatization&globalization) economy, organizations have an increasing responsibility to facilitate, demonstrate and promote corporate social responsibility (CSR). Industries are facing challenging times world-wide. Increased competition and commercial pressure are combining with rising regulatory standards and consumer demand to create a whole new playing field for corporate sectors. Traditional expectations of business are also changing. It is no longer enough to simply employ people, make a profit and pay taxes. Business and industry have come into existence to promote social growth and social good. They draw resources from the society and add values to generate wealth. Hence, society and business are interdependent and business must take full account of societal expectations. Companies are now expected to act responsibly, be accountable and benefit society as a whole. A stable corporate social responsibility is a pre-requisite for business investment and industrial operations.